Neonatal heel prick mass spectrometry identifies metabolic predictors of AML latency. (October 2021) - Lim, Kelly; Thompson-Peach, Chloe; Thomas, Daniel
Abstract: Ongoing research efforts that consider cancer as a disease of dramatically altered cellular metabolism have accelerated interest in snapshot metabolomics in various human tissues. In this issue of Leukemia Research, Petrick et al performed metabolomic analysis on newborn blood spots and found a number of unexpected ceramide and sphingolipid compounds that may play a role in the development and latency of pediatric acute myeloid leukemia (AML). The chemical complexity and range of cellular metabolites massively exceeds the relatively limited building blocks of the transcriptome or the proteome and has high potential to find novel leukemia-specific macromolecular synthesis pathways, metabolic vulnerabilities and biomarkers.